Forest stand maintenance by Farmers of Beringin Jaya Community Forest, Protection Forest Management Unit North Kota Agung, Tanggamus - Bayu Setiawan; Indriyanto Indriyanto; Afif Bintoro (Jurnal Silva Tropika, 2020)
Beringin Jaya Community Forest is one of the community forests in Tanggamus Regency, Lampung Province. The economy of the forest farmers highly depends on the productivity of the forest land. One of the things can be done to improve forest productivity is by doing maintenance in the forest stand. Therefore, research regarding forest maintenance done by forest farmer is significantly important to be conducted. The aim of the research is to figure the maintenance system done by the farmers. The data is collected through direct observation and interview towards 72 respondents. The study shows that 72 farmers (100%) conduct weeds clearing and pruning, while transplanting conducted by 65 farmers (90.3%), 51 farmers (70,8%) apply fertilizer, 24 farmers (33,3%) doing tillage, 14 farmers (19,4%) do pest and disease management. Transplanting technique while they use is by planting seedlings in the hole sized 40cm x 40cm x 40cm during wet season. Tillage is done by tilling the soil around the tree with diameter 20–50 cm, mostly it is done during the dry seasons. Weeding was done conventionally and chemically, 3–4 times per year. Organic and chemical fertilizer is used by the farmers which applied in the wet seasons. Fertilizing is being done by buried the fertilizer around the plants. In the other hand, unproductive branches will be pruned, the pruning was usually done in the wet season. Pest and Disease management conducted by the farmers were by making a trap or hunt the pest down. Keywords: maintenance, community forest, forest farmers.